2021
DOI: 10.3390/nu13113933
|View full text |Cite
|
Sign up to set email alerts
|

Protein Quality in Infant Formulas Marketed in Brazil: Assessments on Biodigestibility, Essential Amino Acid Content and Proteins of Biological Importance

Abstract: Infant formulas, designed to provide similar nutritional composition and performance to human milk, are recommended when breastfeeding is not enough to provide for the nutritional needs of children under 12 months of age. In this context, the present study aimed to assess the protein quality and essential amino acid content of both starting (phase 1) and follow-up (phase 2) formulas from different manufacturers. The chemical amino acid score and protein digestibility corrected by the amino acid score were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…The findings indicated that the texts iron (in “Minerals”), protein (in “Macronutrients”), vitamin (in “Vitamins”), and DHA (in “Lipids”) were frequently mentioned in the FOPs of infant and toddler food products, which aligned with previous studies emphasizing the importance of these nutrients for early childhood development [ 43 – 45 ]. Especially, the observation of iron and protein as the most frequently occurring nutrients in the FOPs of infant foods ( Table 4 ) supported the benefits of these nutrients for the development of infants and toddlers [ 46 48 ], as well as suggested supplementation of iron and protein for breast milk [ 49 ]. The study also exhibited consistent results with previous work by Berry & Gribble [ 50 ], which analyzed health information from online advertisements of infant formula, and the main claims included supporting brain and eye development, bone growth, and immune system, as well as aiding digestion.…”
Section: Discussionmentioning
confidence: 98%
“…The findings indicated that the texts iron (in “Minerals”), protein (in “Macronutrients”), vitamin (in “Vitamins”), and DHA (in “Lipids”) were frequently mentioned in the FOPs of infant and toddler food products, which aligned with previous studies emphasizing the importance of these nutrients for early childhood development [ 43 – 45 ]. Especially, the observation of iron and protein as the most frequently occurring nutrients in the FOPs of infant foods ( Table 4 ) supported the benefits of these nutrients for the development of infants and toddlers [ 46 48 ], as well as suggested supplementation of iron and protein for breast milk [ 49 ]. The study also exhibited consistent results with previous work by Berry & Gribble [ 50 ], which analyzed health information from online advertisements of infant formula, and the main claims included supporting brain and eye development, bone growth, and immune system, as well as aiding digestion.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding the protein quality of the minimally processed and the heated infant formulas, comparable DIAAS values around 0•8 were obtained for T− and Tþþþ due to low aromatic amino acid content, especially tyrosine. Analyses of the amino acid composition of infant formulas have previously reported limited contents of aromatic amino acids, isoleucine, histidine and/or tryptophan (39)(40)(41) . Moreover, the values obtained for the DIAAS were in line with previously reported ones.…”
Section: Discussionmentioning
confidence: 99%
“…Infant formulas are industrialized products prepared using modified milk from cows or other animals or hydrolysate proteins from vegetables, such as soy or rice. Cow milk-derived infant formulas are those that most closely resemble the nutritional and functional characteristics of human milk [ 5 ]. In Brazil, infant formulas are sold mainly in the powdered form packed in aluminum cans, in contrast to the USA and European countries, where these products are commercialized in both powder and liquid form, ready for consumption, as well as in concentrated liquid form for subsequent dilution [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%